The impact of ancestral, genetic, and environmental influences on germline de novo mutation rates and spectra - O. Isaac Garcia-Salinas; Seongwon Hwang; Qin Qin Huang; Rashesh Sanghvi; Daniel S. Malawsky; Joanna Kaplanis; Matthew D. C. Neville; Felix R. Day; Raheleh Rahbari; Aylwyn Scally; Hilary C. Martin (Nature Communications)
Abstract De novo germline mutation is an important factor in the evolution of allelic diversity and disease predisposition in a population. Here, we study the influence of genetically-inferred ancestry and environmental factors on de novo mutation rates and spectra. Using a genetically diverse sample of ~10 K whole-genome sequenced trios, one of the largest de novo mutation catalogues to date, we found that genetically-inferred ancestry is associated with modest but significant changes in both germline mutation rate and spectra across continental populations. These effects may be due to genetic or environmental factors correlated with ancestry. We find epidemiological evidence that cigarette smoking is significantly associated with increased de novo mutation rate, but it does not mediate the observed ancestry effects. Investigation of several other potential mutagenic factors using Mendelian randomisation showed no consistent effects, except for age at  menopause, where factors increasing this corresponded to a reduction in de novo mutation rate. Overall, our study sheds light on factors influencing de novo mutation rates and spectra.